Combined metabolome and transcriptome analysis provides molecular insights into reproductive process in Chuanxiang Black and Landrace pigs - Li, Jiangling; Zhang, Jinling; Zhao, Sujun; Wang, Qiushi; Liu, Rui; Chen, Xiaohui; He, Zhiping (Frontiers in Genetics, 2025)
Testes are crucial for male reproduction, and transcriptomic and metabolomic analyses can help identify genes and pathways linked to reproductive performance differences in pig breeds. The present study was conducted to identify the differentially expressed genes and differentially accumulated metabolites (DAMs) through transcriptomic and metabolomic analyses of testicular tissues in Chuanxiang Black and Landrace pigs. Six testis tissue samples from each pig breed were used for transcriptomic analysis. Further liquid chromatography-mass spectrometry analysis was performed for targeted metabolomic analysis to identify differential metabolites in both breeds. RNA-sequencing data identified a total of 6,233 DEGs, including 3,417 upregulated and 2,816 downregulated genes in Chuanxiang Black compared to Landrace pigs. Comparative pathway enrichment analyses revealed that many DEGs and DAMs were associated with critical reproductive pathways, especially those related to male gametogenesis, spermatogenesis, sexual reproduction, development, and reproductive processes. Three major pathways related to signal transduction (PI3K-Akt, Rap1, and MAPK signaling pathways), lipid metabolism (linoleic acid and arachidonic acid metabolism), and cytokine-cytokine receptor interaction were identified as differentially enriched pathways in Chuanxiang Black pigs. Differential circRNA target gene enrichment analysis revealed 4,179 DEGs, including 3,022 genes involved in biological processes, 477 in cellular components, and 680 in molecular functions. Differential analysis of miRNA between the two groups revealed 2,512 DEGs, including 1,628 upregulated and 884 downregulated genes. Both miRNA and circRNA were involved in enriched KEGG pathways mainly including signaling pathways (cAMP signaling pathways, calcium signaling pathways), endocrine secretion (aldosterone synthesis and secretion and GnRH secretion), and signaling molecules and interaction (ECM-receptor interaction). These findings revealed that both circRNA and miRNA play a crucial role in regulating the differential gene expression related to reproductive processes in Chuanxiang Black compared to Landrace pigs.